Optimal Treatment for Patients With Cavernous Transformation of the Portal Vein - Wei, Bo; Huang, Zhiyin; Tang, Chengwei (Frontiers in Medicine, 2022)
Cavernous transformation of the portal vein (CTPV) is a sequela of extrahepatic and/or intrahepatic portal vein obstruction caused by a combination of local and risk factors. It was ever taken as a relatively rare disease because of its scant literature, which was mainly based on clinical series and case reports. CTPV often manifests as gastroesophageal variceal bleeding, splenomegaly and portal biliopathy after long-term insidious presentation. It is unable for CTPV to be recanalized with anticoagulation because it is a complete obstruction of the mesentericoportal axis. Endoscopic therapy is mainly used for temporary hemostasis in acute variceal bleeding. Meso-Rex shunting characterized by portal-flow-preserving shunts has been widely performed in CTPV children. The multitude of complications associated with CTPV in adults can be effectively addressed by various interventional vascular therapies. With the ubiquity of radiological examinations, optimal treatment for CTPV patients becomes important. Multivisceral transplantation, such as liver-small intestinal transplantation, may be lifesaving and should be considered for patients with diffuse mesenteric venous thrombosis.